Mindfulness-Based Cognitive Therapy for Unmedicated Obsessive-Compulsive Disorder: A Randomized Controlled Trial With 6-Month Follow-Up - Zhang, Tianran; Lu, Lu; Didonna, Fabrizio; Wang, Zhen; Zhang, Haiyin; Fan, Qing (Frontiers in Psychiatry, 2021)
Background: This was the first randomized controlled trial (RCT) designed to test whether the efficacy of Mindfulness-based cognitive therapy (MBCT) is equal to that of the first-line treatment for OCD (SSRIs) or better than that of a placebo with unmedicated obsessive-compulsive disorder (OCD) patients, and also in terms of treatment acceptability and safety. Methods: A total of 123 unmedicated OCD patients with mild to moderate symptoms were randomized into three groups receiving either selective serotonin reuptake inhibitors (SSRIs), an MBCT for OCD program or psycho-education (PE) intervention for 10 weeks. All subjects were evaluated at baseline, mid-intervention, post-intervention and then at 14, 22 and, 34 weeks during follow-up. The primary efficacy measure was Yale–Brown Obsessive-Compulsive Scale (Y-BOCS), with Hamilton Depression Scale-24 (HAMD-24) and Hamilton Anxiety Scale (HAMA) as secondary outcome measures. The Five Facet Mindfulness Questionnaire (FFMQ) and Sheehan Disability Scale (SDS) were used to measure the level of mindfulness and social functions, respectively. Dropout rate and frequency of occurrence were treatment acceptability indicators whereas adverse event (AE) was the treatment safety indicator. Results: The rank sum test showed that the difference between the three conditions in terms of treatment response is significant post-treatment. SSRIs and MBCT were significantly more likely to acquire good treatment results than PE (X2 = 6.448, p = .04) and there is no difference between SSRIs and MBCT (X2 = 1.220, p = .543). Up to the 6-month follow-up there was no significant difference in response results between the three conditions. There was no AE shown in MBCT for OCD. Conclusion: MBCT for OCD is effective in the treatment of unmedicated OCD with mild to moderate symptoms comparable to that of SSRIs, and showed maintenance of improvement at follow-up. It also has good clinical compliance and is suitable and safe for application.